The Role of Digital Services in Improving the Quality of e-KTP Services and User Satisfaction - Tambunan, Heasty Olyvia; Nasution, Nuratikah; Manurung, Rewina F; Simamora, Roma Grecia; Hasanah, Silva Nurul; Irawan, Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Electronic Identity Card (e-KTP) services constitute a strategic form of public service that plays a crucial role in fostering orderly population administration and enhancing the quality of governmental governance. The quality of e-KTP services serves as a primary determinant in shaping public satisfaction as service users, given that the e-KTP functions not only as a legal identity but also as a foundational component of the national population database. This study aims to analyze the role of service delivery in improving the quality of e-KTP services and its implications for user satisfaction. The research employs a literature review method with a descriptive-analytical approach to a number of national scholarly journals that examine e-KTP service quality across various regions in Indonesia. The findings indicate that the quality of e-KTP services, measured through the dimensions of tangibles, reliability, responsiveness, assurance, and empathy, exerts a significant influence on user satisfaction, although the degree of influence of each dimension varies according to regional characteristics and the capacity of service providers. Furthermore, supporting factors such as the availability of facilities and infrastructure, the competence of public officials, procedural clarity, and technology-based service innovations contribute to enhancing perceptions of service quality. Therefore, improving the quality of e-KTP services requires not only technical and administrative improvements but also the strengthening of a user-centered public service orientation.